ئاستى پشتبەستنى پارتە سیاسییەکان بە سۆشیال میدیا لە هەڵمەتى هەڵبژاردن - احمد, پ.ی. د. پاڤێ جمیل; حسن, سەنگەر جمال (Sulaimani Journal for Humanities, 2023)
The main objective of this research entitled is to understand the extent, level, dissection and explanation of the extent of reliance on social media platforms and identifying the instruments depended on. The research community is political parties in Kurdistan Region and the sample of the research is (Kurdistan Coalition), the social media cadres of the political parties within the coalition. The number is (164) participants and they have been chosen on a non-random purposeful manner. utilizes the descriptive method (survey) and the information is collected through the tool of questionnaire. Then, the data, answers of the samples and the relationship between the two main variants and objective are determined through the use of Statistical Package for the Social Sciences (SPSS). Among the most prominent findings of the research are; the extent of reliance of political parties on social media in election campaigns is at a high level, and they depend on social media platforms to a great extent but the greatest reliance of political parties is on (Facebook). The most important reason of the reliance of political parties on social media in election campaigns is the speed of reaching the recipient and encouraging people to vote.
Keywords: الحملات الانتخابية الاحزاب السياسية مواقع التواصل الأجتماعي